(untitled) (Journal of Partial Differential Equations, 2004)
For quasilinear hyperbolic systems with characteristics of constant mul- tiplicity, suppose that characteristics of constant multiplicity(> 1) are linearly degen- erate, by means of generalized normalized coordinates we get the global existence and the blow-up phenomenon of the C¹ solution to the Cauchy problem under an additional hypothesis.